Elastisitas Produk Domestik Regional Bruto Terhadap Belanja Daerah Di Provinsi Sumatera Selatan - Kiagus Zainal Arifin (EKSISTANSI, 2020)
This study aims to determine how large the expenditure elasticity of the district/city in South Sumatra province to the Gross Regional Domestic Product (GDP) of her. In analyzing the problem is with the description and the statical analysis. Data obtained from the Provincial Government and the Central Bureau Stisitk South Sumatra, in the form of time series data and cross section data. To get the elasticity number of economic indicators to the two areas above, the data entered into a linear regression model in the form of logarithms. Logarithmic linear regression model is known as Constant Elasticity. Theoretical basis is a constant elasticity theory and the theory of government spending (government expenditure. The results of the study found that there is a positive relationship between the variables are very closely by local government districts/ cities with GDP district /city. However, the elasticity relationship to them is not elastic (inelastic). This means that although government spending district/city become an inseparable part of the component of regional economic growth, but increase the number of local government spending is not too responded positively by GDP district/city.